Study on fault sealing of the Lishui West Sag in the East China Sea Basin - Yang, Bing; Fu, Qiang; Liu, Jinshui; Ma, Wenrui; Zhao, Shijie (Frontiers in Earth Science, 2023)
The property of fault sealing is a critical controlling factor for hydrocarbon transportation. To date, the sealing property of the complex fault system in the Lishui West Sag is still not clear, meaning it is essential to study regional hydrocarbon transportation and reservoir formation. In this study, we use an integrated method to quantitatively analyze and characterize several important index parameters that affect the sealing property of the faults in the Lishui West Sag based on regional logs and seismic data. We calculated the shale smear factor (SSF), shale gouge ratio (SGR), and clay smear potential (CSP) to characterize the lateral sealing property of the main faults covered with the giant thick shale cap in the Lishui West Sag. We used the vertical shale smear factor Q to clarify the vertical sealing property of these faults quantitatively as a comparison. The results show that the shale cap has a strong smear ability in the Lishui West Sag, while the active fault could moderate the smear. A high fault activity in this area benefits hydrocarbon transportation at the same time. The lateral sealing property and the vertical sealing property of the main faults in the Lishui West Sag have negative correlations.